PERBANDINGAN MODEL GUIDED DISCOVERY LEARNING DENGAN GUIDED INQUIRY TERHADAP HASIL BELAJAR SISWA - Intania Riska Putrie; Arwin Achmad; Berti Yolida (Universitas Lampung, 2015)
The purpose of this research was to know the differences in learning outcomes of students cognitive and affective aspects between Guided Discovery Model with Guided Inquiry Model. The design of this research was the randomized pretest-posttest control group design. The quantitative data were obtained from pretest, posttest, N-gain that were analyzed by t test and U test. The qualitative data were affective aspect which obtained and analyzed descriptively using observation sheet. The result of this research showed that the average N-gain of experiment class II (71.21) with high criteria was better than the experiment class I (43.69) with medium criteria. Then, students result in affective aspect in experiment class II was 71.69 with good criteria, while the experiment class I was 68.75 with enough criteria. Thus, Guided Inquiry model is better than Guided Discovery Learning in improving student learning outcomes.Penelitian ini bertujuan mengetahui perbedaan hasil belajar aspek kognitif dan afektif siswa dalam menggunakan model Guided Discovery dengan Guided Inquiry. Desain penelitian ini menggunakan the randomized pretest-posttest control group design. Data kuantitatif, diperoleh dari pretest, posttest, N-gain yang dianalisis menggunakan Uji-t dan Uji U. Data kualitatif berupa hasil belajar aspek afektif yang diperoleh dari lembar observasi dan dianalisis secara deskriptif. Hasil penelitian menunjukkan rata-rata N-gain kelas eksperimen II (71,21) dengan kriteria tinggi lebih baik dibandingkan kelas eksperimen I (43,69) dengan kriteria sedang. Rata-rata hasil belajar aspek afektif kelas eksperimen II (71,69) berkriteria baik, sedangkan kelas eksperimen I (68,75) berkriteria cukup. Dengan demikian, model pembelajaran Guided Inquiry lebih baik dibandingkan Guided Discovery Learning dalam meningkatkan hasil belajar siswa.Kata kunci: guided discovery learning, guided inquiry, hasil belajar